2023
DOI: 10.1186/s12888-023-05122-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of family function, depression, and self-perceived burden on loneliness in patients with type 2 diabetes mellitus: a serial multiple mediation model

Yu Zhang,
Xiangning Li,
Yaxin Bi
et al.

Abstract: Background Type 2 Diabetes mellitus (T2DM) has become a major lifestyle disease endangering human health worldwide. Patients with T2DM face varying degrees of loneliness, which adversely affects their family and the larger society. This study investigates the serial multiple mediating roles of depression and self-perceived burden between family function and loneliness in the T2DM population of China. Methods In total, 260 T2DM patients were include… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 47 publications
0
1
0
1
Order By: Relevance
“…1 Controlling diabetes is influenced by several factors, such as medication, follow-up management and emotional and social support, as physiological and social functions have a serious negative impact on the mental states of patients with diabetes. 2 Self-perceived burden (SPB) refers to negative emotions such as anxiety, depression and loneliness, which are caused by physical worries about the illness and psychological stress that encompasses feelings of guilt, dependence and fear of imposing a burden on others during the care-receiving process. 3 Recent studies 4 have shown that the frailty arising from chronic diseases among elderly patients is in close connection with SPB.…”
Section: Introductionmentioning
confidence: 99%
“…1 Controlling diabetes is influenced by several factors, such as medication, follow-up management and emotional and social support, as physiological and social functions have a serious negative impact on the mental states of patients with diabetes. 2 Self-perceived burden (SPB) refers to negative emotions such as anxiety, depression and loneliness, which are caused by physical worries about the illness and psychological stress that encompasses feelings of guilt, dependence and fear of imposing a burden on others during the care-receiving process. 3 Recent studies 4 have shown that the frailty arising from chronic diseases among elderly patients is in close connection with SPB.…”
Section: Introductionmentioning
confidence: 99%
“…(5) Se destaca la importancia de abordar la funcionalidad familiar como un factor crítico en la aparición de los síntomas depresivos, y se reconoce a la familia como un espacio crucial con un gran potencial para influir positivamente en la salud y el bienestar de la persona con DT2. (6,7) En este sentido, el enfoque holístico en la atención primaria de enfermería, que incluye la participación activa de la familia en el proceso de saludenfermedad, se considera esencial para comprender y atender las diversas necesidades de la persona con DT2. (8)…”
Section: Introductionunclassified